Hypertrophic effect of inhaled beta2-agonist with and without concurrent exercise training: a randomized controlled trial - Jessen, S.; Onslev, J.; Lemminger, A.; Backer, V.; Bangsbo, J.; Hostrup, M. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Due to a high prevalence of asthma and exercise-induced bronchoconstriction in elite athletes, there is a high use of beta2-adrenoceptor agonists (beta2-agonists) in the athletic population. While anabolic in rodents, no study has been able to detect hypertrophy in humans after chronic beta2-agonist inhalation. Methods: We investigated if inhaled beta2-agonist, terbutaline, alters body composition and metabolic rate with and without concurrent exercise training in healthy young men. Sixty-seven participants completed a four-week intervention of daily terbutaline (8×0.5 mg) or placebo treatment without concurrent training (habitual; n=23), with resistance (n=23) or endurance (n=21) training three times weekly. Before and after the interventions, participant's body composition was determined by dual-energy X-ray absorptiometry, and resting metabolic rate and substrate oxidation by indirect calorimetry. Results: Terbutaline increased lean body mass by 1.03 kg (95%CI 0.29-1.76; p<0.05) and 1.04 kg (95%CI 0.16-1.93; p<0.05) compared to placebo in the habitual and resistance training group, respectively, but had no effect compared to placebo in the endurance training group [-0.56 kg (95% CI -1.74-0.62; p>0.05)]. Fat mass, bone mineral content, and resting metabolic rate did not change differently between treatments with the intervention. Conclusion: Daily inhalation of terbutaline in near-therapeutic doses induces skeletal muscle growth. This observation should be a concern for anti-doping authorities.